Exflagellated microgametes of Plasmodium vivax in human peripheral blood: A case report and review of the literature - Tembhare Prashant; Shirke Shalaka; Subramanian P; Sehgal Kunal; Gujral Sumeet (Wolters Kluwer Medknow Publications, 2009)
Peripheral blood smear examination is the most specific as well as the most common test performed for the diagnosis of malaria. Schizonts, ring forms (trophozoites) and gametocytes are the stages of malarial parasite that are commonly seen in the peripheral blood smear of a patient. Here, we report an extremely rare case of a 40-year-old male patient who presented with Plasmodium vivax infection with multiple exflagellated microgametes in the peripheral blood smear with review of the literature. Exflagellation of microgametes in malarial parasites is only seen in the definitive host, mosquito, and is very unusual to see during the developmental phases in the intermediate host, human. It is important to recognize these exflagellated microgametes in the peripheral blood smear as they may lead to diagnostic confusion with organisms such as spirochetes and trypanosomes.